Seismicity and potencially active faults in the Northwest and Central-West Iberian Peninsula - Martín-González, F.; Antón, L.; Insua, J.M.; De Vicente, G.; Martínez-Díaz, J.J.; Muñoz-Martín, A.; Heredia, N.; Olaiz, A. (Journal of Iberian Geology, 2012)
The Northwest and Central-West Iberian Peninsula configure an intraplate area far from the active plate boundaries, where the Variscan basement crops out extensively (Iberian Massif). This area of the Iberian Peninsula has been traditionally considered a seismically stable region; however, it presents a moderate intraplate seismicity which indicates the presence of active structures and the occurrence of potentially damaging earthquakes. The scarcity of Mesozoic and Cenozoic deposits makes very difficult to track the record of the more recent tectonic activity and the characterization of active tectonic structures within the Iberian Massif. Nevertheless the seismic sequences of 1995-1997 in Lugo (5.1 mb; IV) and 2003 in Zamora (4.2 Mw) provided important information about the orientation of the present stress tensor, and the distribution of the hypocenters informed about the rupture geometry of the fault planes. The present work integrates geological, geomorphological, structural, and seismological data in order to define the main potentially active faults in the region. Faults trending NE–SW to N–S are potentially active as strike-slip, in some cases with a reverse component, under a NW-SE to N–S compression.